Effectiveness of Nutrition Education and Local Food-Based Supplementary Feeding to Improve Maternal Nutritional Status During Pregnancy - Dasmasela, Maya Klementina; Hardinsyah, Hardinsyah; Dewi, Mira; Ekayanti, Ikeu (World Nutrition Journal, 2025)
Background: Chronic Energy Deficiency (CED) among pregnant women remains a significant public health concern in Indonesia. Objectives: This study aimed to evaluate the effectiveness of a 16-week nutrition intervention that integrated Behavior Change Communication (BCC)-based nutrition education with the provision of local food-based supplementary feeding (≥350 kcal/day) in improving the nutritional status of pregnant women.